The Importance of Socio-Emotional Skills for Multiple Life Outcomes and the Role of Education - Barbara Belfi; Lex Borghans (Institute of Labor Economics (IZA), 2025)
In this paper, we explore the interplay between personality traits, socio-emotional skills, and key life outcomes across education, employment, social connectedness, health, and civic participation. Drawing on a rich body of research, we highlight the significant impact of socio-emotional skills, as defined by the Study on Social and Emotional Skills (SSES) framework developed by the Organization for Economic Co-operation and Development (OECD), on various aspects of life. From academic achievement to job performance, social relationships, health indicators, and civic engagement, socio-emotional skills emerge as crucial predictors of success and well-being. Moreover, we examine the effectiveness of educational interventions in fostering socio-emotional skills, considering optimal timing and intervention strategies. Through meta-analyses and empirical studies, we uncover insights into the developmental trajectory of these skills and their malleability over time. These findings have profound implications for policymakers, practitioners, and researchers, emphasizing the importance of integrating socio-emotional skill development into educational curricula and broader societal initiatives. By aligning interventions with the OECD framework and adopting evidence-based practices, stakeholders can empower individuals to navigate life's challenges with resilience and thrive in an increasingly complex world.
Keywords: I20; I31; 330; socio-emotional skills; personality traits; education; interventions; life outcomes